Clinical Outcome of Topical Propolis Treatment in a Feline Cutaneous Wound: A Case Report (Jurnal Riset Veteriner Indonesia (Journal of The Indonesian Veterinary Research), 2026)
A female domestic cat was found with a large wound on the right hind leg, around lateral knee region. The cat was cared for by the rescue team for about two weeks before being taken to the clinic, but they admitted there were no significant changes in the healing process of the wound during self-care. Clinical observation showed that the patient's condition was stable, but the wound was completely covered with granulation tissue and pus. Open wound care was decided as a treatment based on the location of the wound and the presence of necrosis. The therapy given was oral medication in the form of cefixime trihydrate (10 mg/kg BW), dexamethasone (0.1 mg/kg BW), and vitamin B12 (50 mcg/day) for 10 days. Topical propolis was then applied to the wound twice daily for a total 14 days during inpatient to accelerate wound healing. The wound was monitored and showed improvement within 5 days. The reduction in wound surface area was clearly visible after 10 days of treatment, without excessive granulation tissue formation and with minimal scarring. This case report concludes that topical treatment with propolis, as additional therapy, can be considered safe and beneficial for healing wounds in cats.